The job diagnostic survey: A functional tool for South African managers - Billy Boonzaier; Michèle Boonzaier (South African Journal of Business Management, 1994)
Current literature on manpower problems in South Africa has hardly focused on what should be done to improve jobs in order to create job experiences that will fulfil employee goals and organizational goals simultaneously. While the focus has been on the environmental (economic, social, political) and organizational (human resources policies, e.g. affirmative action) components of human resources management, in this article the authors provide guidelines to facilitate a process through which South African managers can practically achieve the optimal fit between current employees and their jobs. A theory that specifies when workers will display motivation, satisfaction and productive behaviour is reviewed. The accompanying diagnostic instrument is presented with South African norms for use by managers of change. Where remedial action is required, guidelines are proposed to assist managers in planning for an enriched work-place. The authors conclude that this approach represents a powerful strategy that can help organizations achieve their goals as well as meeting the needs of contemporary employees for a more meaningful work experience. This approach ensures that changes in the workplace are brought about on the basis of relevant information regarding the characteristics of jobs and the needs of workers, which is, in turn, based upon fundamental psychological rules and buttressed by South African findings that the theory is empirically sound.
Keywords: 650